An empirical study into the limitations and emerging trends of Six Sigma in manufacturing and service organisations. Issue 3 (23rd December 2019) - Antony, Jiju; Sony, Michael
Abstract : Purpose: The purpose of this paper is to carry out an empirical study of the limitations and emerging trends of Six Sigma in manufacturing and service companies. Design/methodology/approach: The authors developed an online survey instrument based on the existing literature addressing the current limitations and emerging trends of Six Sigma in manufacturing and service companies. In this study, 75 Six Sigma Master Black Belts, 39 Black Belts and 12 Green Belts from large manufacturing and service companies participated; each of whom is familiar with the Six Sigma topics. Findings: This study reports the top 5 limitations and emerging trends of Six Sigma from the viewpoints of subject matter experts from large manufacturing and service companies from over 20 countries. The main finding is that the top 4 limitations were identical for both manufacturing and service companies. These limitations include: the integration of Six Sigma with Big Data, the use of Six Sigma in small medium and micro-enterprises, an over emphasis of Six Sigma on variability reduction and the poor implementation of Six Sigma and its resultant negative impact on employee satisfaction. Practical implications: In order to sustain Six Sigma initiatives in organisations, the authors argue that the limitations and emerging trends of this powerful business strategy should be understood and appropriate remedial strategies developed to address said limitations. Originality/value: To the best of the authors' knowledge, this is the first empirical study to examine the limitations and emerging trends of Six Sigma in both manufacturing and service organisations. Moreover, the findings of the study can be very beneficial to many organisations.